Analisis kualitas fisik dan keberadaan mikroplastik pada air minum isi ulang di Kecamatan Medan Selayang tahun 2023 - Siregar, Tasya Aulia Putri; Santi, Devi Nuraini (TROPHICO: Tropical Public Health J., 2025)
Drinking water is vital for daily consumption and having physical qualities that meet health standards is critical. A study (Mason et al.) in 2018 at the University of New York showed that 93% of bottled drinking water contains microplastics. The study used 259 drinking water bottle samples, including those sold in Indonesia from 11 different brands and the size of microplastics found were between 6.5-100 micrometers. Furthermore, microplastics are also found in refillable gallon drinking water that could create microplastics fragments. This study was done to analyze the physical qualities and presence of microplastics in bottled and refillable gallon drinking water in Medan Selayang in 2023. This was a descriptive study with observational and interview methods. There were 12 water samples obtained from simple random sampling. Our study showed that the drinking water physical qualities has met the health standards (100%) as per the regulation of Ministry of Health (Permenkes No.2, 2023). However, the equipment condition in all drinking water depots did not meet the health standards (100%). The processing and cleaning in the drinking water depots have all met the health standards (100%). All samples from drinking water depots contained microplastics in the form of fibers and fragments per liter. It is recommended for water depots in Medan Selayang to pay more attention to the quality of drinking water through physical, chemical, and biological parameters, and to do periodical examination of the water through the public health office.